Efektivitas Mendengarkan Murottal Al-Quran Dalam Menurunkan Tingkat Insomnia Pada Mahasiswa - Masita Aprilini; Ahmad Yasser Mansyur; Ahmad Ridfah (Psikis : Jurnal Psikologi Islami, 2019)
The purpose of this study was to test the effectiveness of listening murottal Quran to reduce insomnia level in student. The research subjects were chosen by purposive sampling technique. The subject of this research were 5 students who experienced insomnia and measured using insomnia severity index. This research using one group pretest-posttest design experiment. Murottal Quran, Surah Ar-Rahman, was heard using MP3 player, with duration of 16.00 minutes for 8 days before bedtime. The results of data testing using Wilcoxon test find a significance level of 0.031 (p <0.05), pretest mean is 17.6, and posttest mean is 11.6. The results show that listening to murottal Quran is effective in reduced insomnia levels in students.